2012
DOI: 10.1186/1471-2377-12-28
|View full text |Cite
|
Sign up to set email alerts
|

Altered small-world properties of gray matter networks in breast cancer

Abstract: BackgroundBreast cancer survivors, particularly those treated with chemotherapy, are at significantly increased risk for long-term cognitive and neurobiologic impairments. These deficits tend to involve skills that are subserved by distributed brain networks. Additionally, neuroimaging studies have shown a diffuse pattern of brain structure changes in chemotherapy-treated breast cancer survivors that might impact large-scale brain networks.MethodsWe therefore applied graph theoretical analysis to compare the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
98
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 61 publications
8
98
1
Order By: Relevance
“…BC chemotherapy is associated with widespread reductions in white matter pathway integrity in similar regions, including cingulum and superior frontal occipital fasciculus (15,16). A previous study from our laboratory demonstrated disorganization of large-scale structural brain networks following BC chemotherapy, including reduced participation of precuneus in the network (17). These neuroimaging findings are supported by animal studies that demonstrate chronic suppression of hippocampal neurogenesis as well as white matter myelin damage following administration of systemic chemotherapeutic agents (1,18).…”
supporting
confidence: 69%
“…BC chemotherapy is associated with widespread reductions in white matter pathway integrity in similar regions, including cingulum and superior frontal occipital fasciculus (15,16). A previous study from our laboratory demonstrated disorganization of large-scale structural brain networks following BC chemotherapy, including reduced participation of precuneus in the network (17). These neuroimaging findings are supported by animal studies that demonstrate chronic suppression of hippocampal neurogenesis as well as white matter myelin damage following administration of systemic chemotherapeutic agents (1,18).…”
supporting
confidence: 69%
“…We have previously observed altered structural and functional clustered connectivity in our cross‐sectional studies of chemotherapy‐treated, long‐term breast cancer survivors (Bruno et al., 2012; Hosseini, Koovakkattu, & Kesler, 2012; Kesler et al., 2015). In the present study, we demonstrated only very subtle disruption of local clustered connectivity in pretreatment patients.…”
Section: Discussionmentioning
confidence: 99%
“…This organization putatively allows the brain to balance the opposing demands of segregation and integration, providing high capacity for parallel information processing with minimal wiring cost (Bassett and Bullmore, 2006). We have previously demonstrated altered organization of gray matter structural and intrinsic functional connectomes in breast cancer survivors (Bruno, et al, 2012; Hosseini, et al, 2012b). For the present study, we expand upon these findings by using DTI-based connectome graphs to evaluate the brain network's tolerance to simulated neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%